A Randomly Amplified Polymorphic DNA Marker Specific for the Bacillus cereus Group Is Diagnostic for Bacillus anthracis - Daffonchio, Daniele (American Society for Microbiology, 1999)
Aiming to develop a DNA marker specific for Bacillus anthracis and able to discriminate this species from Bacillus cereus, Bacillus thuringiensis, and Bacillus mycoides, we applied the randomly amplified polymorphic DNA (RAPD) fingerprinting technique to a collection of 101 strains of the genus Bacillus, including 61 strains of the B. cereus group. An 838-bp RAPD marker (SG-850) specific for B. cereus, B. thuringiensis, B. anthracis, and B. mycoides was identified. This fragment included a putative (366-nucleotide) open reading frame highly homologous to the ypuA gene of Bacillus subtilis. The restriction analysis of the SG-850 fragment with AluI distinguished B. anthracis from the other species of the B. cereus group.